2020
DOI: 10.1016/j.bbrep.2020.100824
|View full text |Cite
|
Sign up to set email alerts
|

Mitofusin-2 mediates doxorubicin sensitivity and acute resistance in Jurkat leukemia cells

Abstract: Mitochondria oscillate along a morphological continuum from fragmented individual units to hyperfused tubular networks. Their position at the junction of catabolic and anabolic metabolism couples this morphological plasticity, called mitochondrial dynamics, to larger cellular metabolic programs, which in turn implicate mitochondria in a number of disease states. In many cancers, fragmented mitochondria engage the cell with the biosynthetic capacity of aerobic glycolysis in service of proliferation and progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…For instance, upregulated OPA1 confers resistance to cytochrome c release upon prolonged venetoclax treatment in acute myeloid leukemia (AML) cells [ 118 ]. Consistently, upregulated MFN2 and increased OXPHOS have been found in cancer cells that survive chemotherapy [ 119 , 120 ]. Several other factors have been reported to promote cancer drug resistance by triggering mitochondrial fusion.…”
Section: Mitochondrial Stress Adaptation and Drug Resistancementioning
confidence: 68%
“…For instance, upregulated OPA1 confers resistance to cytochrome c release upon prolonged venetoclax treatment in acute myeloid leukemia (AML) cells [ 118 ]. Consistently, upregulated MFN2 and increased OXPHOS have been found in cancer cells that survive chemotherapy [ 119 , 120 ]. Several other factors have been reported to promote cancer drug resistance by triggering mitochondrial fusion.…”
Section: Mitochondrial Stress Adaptation and Drug Resistancementioning
confidence: 68%
“…It has been demonstrated that venetoclax-resistant AML cells are also resistance to cytochrome c release whenever stimulated due to upregulation of OPA1 [458,459]. Since MFN2 deletion greatly enhances Jurkat doxorubicin sensitivity, MFN2 and OXPHOS have been discovered to be considerably elevated in surviving leukemia cells [460,461]. It has been discovered that suppressing MFN1 improves cisplatin sensitivity in human neuroblastoma cells by inhibiting mitochondrial fusion [462].…”
Section: Mitochondrial Fusion and Fissionmentioning
confidence: 99%
“…In particular, venetoclax-resistant AML cells show upregulation of OPA1, which likely establishes resistance to cytochrome c release upon stimulation [ 68 ]. In accordance with the role of mitochondrial fusion in chemoresistance, MFN2 and oxidative phosphorylation (OXPHOS) have been found to be significantly upregulated in surviving leukemia cells since the knockout of MFN2 substantially increases Jurkat sensitivity to doxorubicin [ 69 ]. In addition, it has been found that the inhibition of mitochondrial fusion by silencing MFN1 increases cisplatin sensitivity in human neuroblastoma cells [ 70 ].…”
Section: Role Of Mitochondrial Remodeling (Fusion Fission Mitophagy and Transfer) In Cancer Chemoresistancementioning
confidence: 99%